P706 A distinct subset of tissue-resident Th17 cells expands in the inflamed intestines of Crohn's Disease patients and responds to colitogenic bacteria. (21st January 2022) - Paroni, M; Leccese, G; Ranzani, V; Pagani, M; Landini, P; Vecchi, M; Abrignani, S; Facciotti, F; Caprioli, F; Geginat, J
Abstract: Background: Inflammatory bowel diseases (IBDs) are characterized by excessive inflammatory T-cell responses to intestinal microbes. Th17-derived Th1 cells ("Th1/17") are pathogenic in mice, and might also drive inflammation in IBDs.Here, we characterized the role of a novel subset of human intestinal-resident Th17 cells, which produced very high levels of IL-17, together with IFN-γ, in intestinal inflammation in Crohn's Disease. Methods: CD4 + T-cell subsets from IBD patients and controls were analysed by RNA sequencing and flow cytometry. They were monitored pre/post-therapies in different tissues, and analysed for antigen specificities. Results: CCR6 + CCR5 + CXCR3 - T-helper cells co-expressed RORC and T-bet, and co-produced IL-17 and IFN-γ. These CCR5 + Th17-cells were associated with intestinal inflammation in Crohn's Disease (CD), but not in ulcerative colitis, and contracted upon Infliximab-induced mucosal healing. Conversely, CXCR3 + CCR6 + Th1/17 cells, which also co-produced IL-17 and IFN-γ, were unaltered. Intestinal CCR5 + Th17-cells had up-regulated genes of pro-inflammatory Th17-effector cells, and down-regulated genes involved in recirculation. Consistently, CCR5 + Th17-cells were rare in peripheral blood and lymph nodes, displayed a tissue-resident phenotype in the gut and were enriched in the intra-epithelial compartment of CD patients. Conversely, CCR5 - Th17-cells were abundant in the circulation, had an increased gut-homing potential in IBDs, and decreased post-Vedolizumab treatment in the intestine. Moreover, they up-regulated CCR5 with IL-23, which was abundant in the guts of CD patients. Importantly, intestinal CCR5 + Th17 cells were selectively activated by adherent-invasive Escherichia coli (AIEC), but not by a commensal/probiotic strain. Th1/17-cells responded instead to Cytomegalovirus. Notably, AIEC induced also IL-23 and the CCR5 ligand RANTES from dendritic cells (DCs). Conclusion: We identified a gut-resident Th17-cell subset that was activated by CD-associated bacteria, suggesting a key role in pathogenesis. They could differentiate from conventional, circulating Th17-cells that are recruited to the gut and activated by AIEC-infected DCs. Conversely, intestinal Th1/17-cells may protect CD patients from CMV-induced colitis.